West Africa facing the lack of traffic lanes - Benjamin Steck (EchoGéo)
This paper aims to contribute to a better understanding of the role of roads as instruments of development.  African countries have to face the lack of asphalt roads. Without such roads, the flows of goods are limited and people are unable to access easily to education, health, food and all the services. Opening new asphalt roads is one of the main challenges for the future years. The case of the Nouakchott-Nouadhibou road, in Mauritania, opened in 2004, is a fruitful example of the effects of such an infrastructure. The traffic is increasing. Many new settlements appear. The Imraguen can have better access to all the services. Beyond those effects, this road is of main interest because of its proximity to a national park, the Banc d’Arguin national Park, which is one of the most important in West Africa. The protection policy involves regulations restricting access to certain areas and prohibiting certain types of exploitation of natural and archaeological resources. The question at least is how African countries can link economic and social purposes with ecological protection for an improvement of human conditions of life. An asphalt road is a means of it but it can also be an instrument of destruction.